Association Between Alcohol Consumption and Academic Achievement: a Cross-sectional Study. - Dong Jun Sung; Wi-Young So; Taikyeong Ted. Jeong; Sung, Dong Jun; So, Wi-Young; Jeong, Taikyeong Ted (Central European Journal of Public Health, 2016)
Aim: Alcohol consumption among adolescents is a serious public health problem in South Korea. Our study examined the relationship between alcohol consumption and academic achievement in Korean adolescents. In 2011, 75,643 students from seventh to twelfth grade participated in the Seventh Korea Youth Risk Behaviour Web-based Survey (KYRBWS-VII).Method: We performed multivariate logistic regression analysis to examine the associations between alcohol consumption, frequency of severe alcohol intoxication, and academic achievement for both girls and boys.Results: Compared to non-drinkers, the odds of achieving average or higher academic performance significantly decreased for both boys and girls with increasing number of days per month with reported alcohol consumption (p≤0.008). Further, odds of achieving average or higher academic performance significantly decreased with increasing amounts of alcohol consumed compared to non-drinkers (p≤0.026). Additionally, the odds of achieving average or higher academic performance according to the frequency of severe alcohol intoxication were only significantly decreased for 1-2 days per month of severe intoxication (p<0.001).Conclusion: Both boys and girls with increased alcohol consumption and frequency of severe alcohol intoxication had below average academic achievement in Korea. To improve academic achievement, we recommend interventions that reduce alcohol consumption among adolescents.